Diagnosis of sessile serrated adenomas/polyps with image-enhanced endoscopy: a systematic review and meta-analysis - Parikh, Neil D.; Chaptini, Louis; Njei, Basile; Laine, Loren (Endoscopy, 2016)
Background and study aims: Distinguishing sessile serrated adenomas/polyps (SSA/Ps) from non-neoplastic tissue may be challenging when white-light endoscopy (WLE) is used. Image-enhanced endoscopy (IEE) has shown accuracy in differentiating adenomas from hyperplastic polyps. The aim of this systematic review and meta-analysis was to evaluate the utility of IEE in diagnosis of SSA/Ps.Methods: Studies were eligible if: they included patients undergoing colonoscopy with an endoscopy-based image-enhancement modality; endoscopic diagnoses, including SSA/P, were based on the appearance of polyps at IEE; and the corresponding histologic diagnoses of polyps were provided. The primary outcome was sensitivity of IEE for SSA/Ps differentiated from non-neoplastic lesions (primary convention) and differentiated from all non-SSA/P lesions, including adenomas (secondary convention). Results: 13 studies met inclusion criteria. Sensitivity ranged from 38 % to 100 % but sensitivity ≥ 90 % was seen in 4 of 10 narrow band imaging (NBI) or magnification-NBI studies. Pooled sensitivities for discriminating SSA/Ps from non-neoplastic lesions were 80 % for magnification-NBI, 60 % for NBI, 49 % for autofluorescence, and 47 % for flexible spectral imaging color enhancement. In head-to-head comparisons with WLE, NBI (89 % vs. 75 %) and magnification-NBI (78 % vs. 63 %) demonstrated significantly greater sensitivity, while autofluorescence imaging (56 % vs. 66 %), flexible spectral imaging color enhancement (100 % vs. 100 %), and high-resolution endomicroscopy (88 % vs. 100 %) did not. Conclusion: IEE currently cannot be recommended as a diagnostic tool for SSA/P. While NBI studies showed promise, more IEE studies employing validated SSA/P criteria in well-defined polyp populations are needed. IEE studies assessing SSA/P detection rates at colonoscopy are also needed.